If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=-3(k-3)
We move all terms to the left:
9-(-3(k-3))=0
We calculate terms in parentheses: -(-3(k-3)), so:We get rid of parentheses
-3(k-3)
We multiply parentheses
-3k+9
Back to the equation:
-(-3k+9)
3k-9+9=0
We add all the numbers together, and all the variables
3k=0
k=0/3
k=0
| (4/5)x=-18 | | j/6+49=55 | | 8-4x=4x-48 | | 2+2x=4x+20 | | -66=-2+4n | | 2x-x=7=x=3+4 | | 3√x√x=3 | | 2+3j=17 | | 16+3x-2x=-6x-x | | 8+4x=-x+48 | | x+.5x+.05x=100 | | 2/3x-4=-4x+10 | | 0.20x+0.25(50)=28.5 | | -5x+10=-7x-2 | | .5x+5x+10x=100 | | 10=f/3+7 | | 4+4x=-4x+68 | | 2g-4.2=-6.4 | | 133=7+9m | | 8x=-16/5 | | 2+4b=14 | | 11x3-50=-17 | | -4x/3-1=13 | | 4.6+10m=8.91 | | 7^15-(7^x)=0 | | 7^15-7^x=0 | | 24x(24-x)=2592 | | 84=-3(x-8) | | h/5.15=-2.2 | | 3(2y)+4y=10 | | 31(x+9)-19x=15(x+11) | | (-4)+3.8t=4.36 |